Standard-Dose Rituximab as Effective Therapy for Treating Malignancy-Related Hemophagocytic Lymphohistiocytosis in the Eldery: A Case Report - Blessie Elizabeth Nelson; Angelina Hong; Mhair Dekmezian; Bagi Jana (Case Reports in Oncology, 2021)
Hemophagocytic lymphohistiocytosis (HLH) is a syndrome involving uncontrolled inflammation due to widespread activation of immune response. HLH can be inherited or acquired secondary to infection, autoimmune, or oncologic processes such as small lymphocytic lymphoma (SLL) or chronic lymphocytic leukemia (CLL). There has been minimal documentation of HLH secondary to SLL/CLL, and results of treatment have been largely unsuccessful. This case describes a critically ill elderly patient with HLH caused by SLL/CLL who was successfully treated with standard-dose rituximab and regained a high quality of life.